SYSTEMATIC LITERATURE REVIEW: KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP DITINJAU DARI ADVERSITY QUOTIENT - Komariah, Nurul; Suryadi, Didi; Nurjanah, Nurjanah (Mathematics Education And Application Journal (META), 2024)
AbstractMathematics is an essential subject that is taught at every level of school. Problem-solving is one of the abilities that must be possessed in learning mathematics. Problem-solving ability is a person's ability to solve a problem whose solution method is not previously known. Intelligence can affect students' problem-solving ability, including intelligence in dealing with problems (adversity quotient). Adversity quotient is classified into three types: climber, camper, and quitter. This study uses a systematic literature review to analyze previous studies examining problem-solving ability and adversity quotient. Some of the article criteria used are journal articles indexed by Sinta or Google Scholar and published in the last 10 years. This study aims to analyze the relationship between students' problem-solving abilities according to Polya's indicators judging from the adversity quotient category of junior high school students. Based on the results of the study, it is found that climber students can master all four Polya indicators, camper students can master three Polya indicators, and quitter students can only master one Polya indicatorKeywords: adversity quotient, problem-solving abiliy, systematic literature review.AbstrakMatematika termasuk mata pelajaran penting yang diadakan di setiap jenjang pendidikan. Kemampuan pemecahan masuk ke dalam salah satu kemampuan yang wajib dikuasai dalam pembelajaran matematika. Kemampuan pemecahan masalah adalah kemampuan seseorang dalam menyelesaikan suatu permasalahan yang metode penyelesaiannya belum diketahui sebelumnya. Kecerdasan dapat mempengaruhi kemampuan pemecahan masalah siswa, termasuk kecerdasan dalam menghadapi masalah (adversity quotient). Adversity quotient dikelompokkan ke dalam tiga jenis yakni climber, camper, dan quitter. Penelitian ini menggunakan teknik analisis data kualitatif dengan metode systematic literature review untuk menganalisis penelitianpenelitian sebelumnya yang mengkaji tentang kemampuan pemecahan masalah dan adversity quotient. Kriteria artikel yang digunakan beberapa diantaranya adalah artikel jurnal yang terindeks Sinta atau Google Scholar dan dipublish 10 tahun terakhir. Penelitian ini bertujuan untuk menganalisis hubungan kemampuan pemecahan masalah siswa menurut indikator Polya dilihat dari kategori adversity quotient siswa SMP. Berdasarkan hasil kajian didapatkan bahwa siswa climber dapat menguasai keempat indikator Polya, siswa camper dapat menguasai tiga indikator Polya, sedangkan siswa quitter hanya menguasai satu indikator Polya.Kata kunci:  adversity quotient, kemampuan pemecahan masalah, systematic literature review.